2012
DOI: 10.1088/0031-8949/86/04/045101
|View full text |Cite
|
Sign up to set email alerts
|

Isgur–Wise function for heavy–light mesons in theD-dimensional potential model

Abstract: This letter reports some improvement of the formalism and analysis of our very recent work [1] on the studies of Isgur-Wise function for heavy-light mesons following higher dimensional string inspired potential model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
(56 reference statements)
1
16
0
Order By: Relevance
“…This Nambu-Goto potential in higher dimension is analogous to the linear plus Coulombic type Cornell potential in 3 + 1 dimensional QCD. Earlier, we have developed similar formalism considering Lüscher term as parent in perturbation technique [53]. However, physical basis of string potential model supports the fact that the linear confinement term as the main contributing part in inter-quark potential and Lüscher's term arises in this potential as a first order correction to the linear confinement term σr [13].…”
Section: Introductionmentioning
confidence: 80%
“…This Nambu-Goto potential in higher dimension is analogous to the linear plus Coulombic type Cornell potential in 3 + 1 dimensional QCD. Earlier, we have developed similar formalism considering Lüscher term as parent in perturbation technique [53]. However, physical basis of string potential model supports the fact that the linear confinement term as the main contributing part in inter-quark potential and Lüscher's term arises in this potential as a first order correction to the linear confinement term σr [13].…”
Section: Introductionmentioning
confidence: 80%
“…The meson wave function within string inspired potential model considering Lüscher (− γ r ) term as parent and linear term (σr) as perturbation (with µ 0 = 0)has been reported in [17,18] as:…”
Section: Mass With Lüscher Term As Parentmentioning
confidence: 99%
“…The surface element in D spatial dimension is DC D r D−1 dr, where the explicit expression of the terms C D has been stated in section 2.1. As the wave function in this case contains Airy's infinite polynomial series, we calculate < H > through numerical integration using the following integrals: (27) In this case, with Airy's function involved in the wave function, simpler equations like (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) in the large D limit are not possible as we follow numerical integration to evaluate terms < H 1 >, < H 2 >, < H 3 >.…”
Section: Mass With Linear Term As Parentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we propose a simpler form of analytic solution of Schrodinger equation with Cornell potential. Our earlier work with Cornell potential using perturbation technique [15][16][17]72,73], considering its linear confinement term as parent, we have found that Airy's infinite polynomial function appears in the solution for wave function. Based upon our past study, here we construct the analytic form of the meson wave function for linear plus Coulombic potential in terms of Airy's function.…”
Section: Introductionmentioning
confidence: 99%